PENGARUH LIFESTYLE, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA MATAHARI LOMBOK EPICENTRUM MALL - Muhammad Zar Ghipari; H. M. Ilhamuddin; Rusminah HS (Fakultas Ekonomi Universitas Islam Al-Azhar, 2022)
This study aims to determine the effect of lifestyle, product quality and promotion on purchasing decisions at Matahari Lombok Epicentrum Mall. The data collection method used is a survey sample with a sampling technique using purposive sampling with a sample of eighty people. Data collection techniques using online questionnaires with data collection tools using questionnaires that have been tested for validity and reliability. The analysis technique used is multiple linear regression. The results showed that the lifestyle variable had a t count value of 2.694 which was greater than the t table with a value of 1.99006 with a significant level of 0.009 having a positive and significant effect on purchasing decisions, the product quality variable had a t count value of 2.159 which was greater than the t table with a value of 2.159. 1.99006 with a significant level of 0.003 has a positive and significant effect on purchasing decisions, and the promotion variable has a t value of 5.881 which is greater than t table with a value of 1.99006 with a significant level of 0.000 a positive and significant effect on purchasing decisions, it can be said all variables have a positive and significant effect.